2018
DOI: 10.4103/ortho.ijortho_469_16
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcome of Modified Weaver Dunn Technique for Acromioclavicular Joint Dislocation

Abstract: Background:The debate about the ideal surgical procedure for acromioclavicular joint (ACJ) dislocation is still unresolved and newer techniques are being evolved continuously. The present study evaluates functional outcome of ACJ reconstruction using the modified Weaver Dunn procedure.Materials and Methods:35 patients (26 males, 9 females) with ACJ dislocation, between the age group of 18–48 years (mean age 31 years), were operated using modified Weaver Dunn procedure at our center from May 2005 to June 2010. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…The original WD procedure included a lateral clavicle resection, reduction of the dislocated clavicle, and transfer of the coracoacromial ligament to the lateral clavicle without additional fixation [33]. Later, numerous studies discussed modified WD procedures using various additional fixation devices intended to provide further stability and maintain reduction of the AC joint, in which satisfactory clinical and radiological outcomes were achieved [32,[34][35][36]. One study reported that 75% of the modified WD procedures had good to excellent results [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…The original WD procedure included a lateral clavicle resection, reduction of the dislocated clavicle, and transfer of the coracoacromial ligament to the lateral clavicle without additional fixation [33]. Later, numerous studies discussed modified WD procedures using various additional fixation devices intended to provide further stability and maintain reduction of the AC joint, in which satisfactory clinical and radiological outcomes were achieved [32,[34][35][36]. One study reported that 75% of the modified WD procedures had good to excellent results [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…But grade 3-6 (high grade injuries) need surgical management. 5,6 More than 150 varieties of surgeries have been reported to treat symptomatic acromioclavicular joint dislocation and greater than 60 unique methods have been reported for the reconstruction of coracoclavicular ligaments after a chronic injury. 3,7 But the best reconstructive method has still not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…8 Frequently used techniques for treatment of Acromioclavicular joint dislocation are fixation by screws or wires or sutures or plate along with repair of ligaments. 5,6,9 "Originally described by James Weaver and Harold Dunn in 1972, the Weaver-Dunn procedure (WD) involves transfer of the coracoacromial (CA) ligament from the acromion to lateral end of the clavicle.in their original series, Weaver and Dunn reported a failure rate of 28%". 9 Shoji et al suggested harvesting of Coracoacromial ligament along with acromion bone to strengthen the repair.…”
Section: Introductionmentioning
confidence: 99%
“…3 These techniques can be classified into three categories: (1) AC joint fixation, which can be done along with repair of ligaments; (2) coracoclavicular (CC) joint fixation using screw/anchors/free tendon graft with AC joint reconstruction; and (3) excision of distal part of clavicle along with CC ligament reconstruction. [3][4][5] The original WD technique described in 1972 involved excising the distal end of the clavicle, release of the coracoacromial (CA) ligament from the acromion, and transferring that portion to the superior aspect of the distal end of the clavicle. [3][4][5][6] Compared with the original CC ligament strength, this ligament reconstruction is markedly weaker and showed clinical failure rates as high as 30%.…”
mentioning
confidence: 99%
“…3 Because of such high failure rates, many modifications have been made to the Weaver-Dunn procedure. [3][4][5][6] The modified Weaver-Dunn (mWD) has many biomechanical advantages in treatment including (1) anatomic reduction, (2) improved protection of CA and CC ligaments, and (3) improved strength and stability of repair comparable with normal anatomy with horizontal and vertical stability. 3,7 In addition, strong clinical outcomes have been reported.…”
mentioning
confidence: 99%